2018
DOI: 10.3389/fpsyg.2018.02088
|View full text |Cite
|
Sign up to set email alerts
|

Materialism, Body Surveillance, Body Shame, and Body Dissatisfaction: Testing a Mediational Model

Abstract: The present study aimed to examine the mechanisms underlying the links between materialism and body dissatisfaction. A sample of 583 Chinese undergraduate women completed a questionnaire measuring materialism, body surveillance, body shame, and body dissatisfaction. Correlational analysis showed that materialism, body surveillance, and body shame were significantly positively correlated with body dissatisfaction. The results of path analyses revealed that higher materialism predicted more body dissatisfaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
3
12
0
1
Order By: Relevance
“…Consequently, as Gruenfeld et al (2008) proposed, having power could enhance objectification and partner objectification as well as sexually coercive behaviors, whereas lacking power could be related to the incapacity to reject unwanted sex after being objectified by a partner. A variable other than the direct or behavioral effects of interpersonal or partner objectification that could be added into future studies could be the emotions and cognitions (inferences) women feel after being objectified, specifically because a previous work has shown the negative association between body surveillance and dissatisfaction because of body shame (Sun, 2018).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Consequently, as Gruenfeld et al (2008) proposed, having power could enhance objectification and partner objectification as well as sexually coercive behaviors, whereas lacking power could be related to the incapacity to reject unwanted sex after being objectified by a partner. A variable other than the direct or behavioral effects of interpersonal or partner objectification that could be added into future studies could be the emotions and cognitions (inferences) women feel after being objectified, specifically because a previous work has shown the negative association between body surveillance and dissatisfaction because of body shame (Sun, 2018).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…The former is related to persistent negative feelings and thoughts about one’s body when it is not consistent with sociocultural standards [ 19 ], while perfectionism is often associated with unrealistically high expectations and overly critical self-assessments [ 20 ]. With reference to the abovementioned outcomes, earlier studies indicated that: (a) body dissatisfaction and body image avoidant behaviours are strongly related to body shame [ 21 , 22 , 23 , 24 ]; and (b) the greater the maladaptive perfectionism, the higher the negative body image [ 25 , 26 ]. Referring to point b above, it is worth noting that research so far has not focused directly on the relationship between perfectionism and body shame, and as we know, unrealistic expectations held by children and adolescents and an overly critical attitude toward oneself may significantly disturb their psychological functioning [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to point b above, it is worth noting that research so far has not focused directly on the relationship between perfectionism and body shame, and as we know, unrealistic expectations held by children and adolescents and an overly critical attitude toward oneself may significantly disturb their psychological functioning [ 27 , 28 ]. However, it can be concluded that a negative cognitive attitude toward one’s body may promote the tendency to avoid dealing with one’s body as well as increase negative emotions toward one’s body (including fear and shame), and that the at-risk group may be people with a strong perfectionist tendency (for whom it is extremely important to meet societal expectations and achieve set standards in many areas of life) [ 1 , 21 , 22 , 23 , 24 , 25 , 26 ]. Importantly, however, most of the abovementioned studies have been conducted in adults and have not considered the dyadic perspective in explaining child and adolescent functioning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, item four was excluded because of its content, since people who experienced body shame do not simply feel dissatisfied with their bodies. They feel contemptuous of their body and wants to change it at any cost [1,32,33]. After modifications, refined reduced models showed adequate estimates of validity and reliability; therefore, they were considered the most appropriate for the data.…”
Section: Discussionmentioning
confidence: 99%